2022
DOI: 10.1126/sciadv.abo0340
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial proteostasis stress in muscle drives a long-range protective response to alleviate dietary obesity independently of ATF4

Abstract: Mitochondrial quality in skeletal muscle is crucial for maintaining energy homeostasis during metabolic stresses. However, how muscle mitochondrial quality is controlled and its physiological impacts remain unclear. Here, we demonstrate that mitoprotease LONP1 is essential for preserving muscle mitochondrial proteostasis and systemic metabolic homeostasis. Skeletal muscle–specific deletion of Lon protease homolog, mitochondrial (LONP1) impaired mitochondrial protein turnover, leading to muscle mitochondrial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
(154 reference statements)
0
21
0
Order By: Relevance
“…We selected ‘resistance exercise studies’ and restricted the analyses to 0 to 6 hours post-exercise, without any other participant criteria, to obtain a high statistical power and a large sample size (n = 148). Genes from each of the pathways of interest (Figure 6.A) were manually curated based on previous literature (Pakos-Zebrucka et al ., 2016; Trewin et al ., 2018; Bishop et al ., 2019; Huertas et al ., 2019; Guo et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected ‘resistance exercise studies’ and restricted the analyses to 0 to 6 hours post-exercise, without any other participant criteria, to obtain a high statistical power and a large sample size (n = 148). Genes from each of the pathways of interest (Figure 6.A) were manually curated based on previous literature (Pakos-Zebrucka et al ., 2016; Trewin et al ., 2018; Bishop et al ., 2019; Huertas et al ., 2019; Guo et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Gene-set enrichment analyses (GSEA) was performed using the R package fast geneset enrichment analysis ( FGSEA ) (Korotkevich et al ., 2021). Mitochondrial-specific genesets were utilised (obtained from the MitoCarta 3.0 (Rath et al ., 2021)) and the mitochondrial unfolded protein response (UPR mt ) geneset was obtained from a mouse study (Guo et al ., 2022). An adjusted p-value lower than 0.05 was deemed significant and enrichment values are reported as normalised enrichment scores (NES).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported that Lonp1 ablation in mouse muscle induces UPRmt activation, leading to adipose tissue and liver metabolism modulation. Functionally, in this model not only the well-known mitochondrial protein turnover alterations can be observed, but also improved insulin resistance, reduced liver steatosis and prevention of high-fat diet (HFD)-induced obesity [ 135 ]. Furthermore, following Lonp1 ablation, muscles are forced to secrete myokines, especially FGF21 and GDF15, to exert endocrine effects, which can contrast diet-induced obesity and generates a positive effect on metabolism [ 136 , 137 , 138 , 139 , 140 ].…”
Section: The Functions Of Lonp1 In the Skeletal Musclementioning
confidence: 99%
“…Guo and colleagues showed that, upon HFD feeding, Lonp1 knockout mice are characterized by reduced lean and fat mass, leading to lower body weight [ 101 , 135 ], smaller adipocytes in adipose tissue, higher mitochondrial respiration and oxidation, increased expressions of genes related to thermogenesis, and lipolysis. Conversely, there is a decrease in fatty acid synthase (FASN) protein levels and de novo lipogenesis, leading to protection from diet-induced hepatic steatosis.…”
Section: The Functions Of Lonp1 In the Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation